Determination of the relationship between NDVI and oil palm yield / Muhammad Azim Kamaruddin - Kamaruddin, Muhammad Azim (2018)
Oil palm is one of the crops that has high economic demand and potential for Malaysia export business. The use of NDVI as a platform to determine the greenness of vegetation has been widely introduced to monitor such crops. Because of the platform used is based on remotely sensed data, such relationship need to be determine between NDVI and oil palm to prove the use of NDVI manage to estimate the oil palm yield. Such estimation can warn the decision makers about potential reduction in crop yields and allow timely import and export decision. Remote sensing data has the potential and capability to provide spatial information for large scale plantation. Compared to ground data, remote sensing offers a simpler way of yield estimation by using satellite image. The relevant of this research is to apply the use of remote sensing in the determination of relationship between the use of NDVI with oil palm yield. This research will be using Normalized Difference (NDVI) to produce NDVI maps and determine the relationship between oil palm yield with respect of the maps produce. The aim of this study is to determine relationship between NDVI and oil palm yield. The study area of this research is at oil palm plantation in Ladang Ayer Hitam, Negeri Sembilan. The data of Sentinel-2 satellite image with 10 meter resolution and yield data of oil palm is used in this study. Processing is carried out using ERDAS Imagine software and the map produced is by using ArcMap. This research method utilizes NDVI by classify the value obtained into three categories (healthy, non-healthy and non-vege area). Regression analysis is done in order to analyze the relationship between NDVI and oil palm yield. The relationship was used to estimate the yield and to analyze the pattern production of oil palm over the study area for year 2015, 2016 and 2017.